PENGARUH KEPUASAN KONSUMEN DENGAN LOYALITAS KONSUMEN RITEL MODERN SPORTS STATION MALL SKA PEKANBARU - Putri Clawson; Pebriadi (P3M STKIP 'Aisyiyah Riau, 2015)
Modern retail is a place that offers a variety of community needs. Retail trade not only sells products, but retail sales also means selling services, so it is natural for retailers to compete for consumers both from products and to offer services. This competition between modern retail and traditional markets requires efforts to maintain customer loyalty so that traders do not lose consumers. In this research, it will be discussed matters relating to customer loyalty, namely customer satisfaction. The purpose of this study is to determine the effect of consumer satisfaction with consumer loyalty in modern retail and to determine the effect of free variables of customer satisfaction with consumer loyalty in modern retail. This research was conducted at SKA Pekanbaru Sports Station Mall in April to May 2015. The sample of this study amounted to 70 people with simple random sampling technique with the subject criteria is the Sports Station Mall SKA Pekanbaru customer. The data collection of this study was carried out using a questionnaire namely the scale of consumer loyalty and customer satisfaction made by researchers. The results of the study at a significance level of 5% indicate that there is a significant influence between consumer satisfaction with customer loyalty in modern retail. The results of partial calculations show that there is a significant positive effect between customer satisfaction and customer loyalty.